2019
DOI: 10.1016/j.antiviral.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

HCMV modulation of cellular PI3K/AKT/mTOR signaling: New opportunities for therapeutic intervention?

Abstract: Human cytomegalovirus (HCMV) remains a major public health burden domestically and abroad. Current approved therapies, including ganciclovir, are only moderately efficacious, with many transplant patients suffering from a variety of side effects. A major impediment to the efficacy of current anti-HCMV drugs is their antiviral effects are restricted to the lytic stage of viral replication. Consequently, the non-lytic stages of the viral lifecycle remain major sources of HCMV infection associated with transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 158 publications
(213 reference statements)
1
20
0
Order By: Relevance
“…The virus engages various cellular entry receptors, several of which activate similar pathways relevant to the IE phase of infection [145][146][147][148][149]. In particular, epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor alpha and integrins independently trigger the phosphatidylinositol 3-phosphate and protein kinase B (PI3K/AKT) pathway [150][151][152]. The PI3K/AKT pathway is central to many cellular properties including motility, proliferation and survival [153][154][155].…”
Section: Transcriptional Control Of the Major Ie Genementioning
confidence: 99%
“…The virus engages various cellular entry receptors, several of which activate similar pathways relevant to the IE phase of infection [145][146][147][148][149]. In particular, epidermal growth factor receptor (EGFR), platelet-derived growth factor receptor alpha and integrins independently trigger the phosphatidylinositol 3-phosphate and protein kinase B (PI3K/AKT) pathway [150][151][152]. The PI3K/AKT pathway is central to many cellular properties including motility, proliferation and survival [153][154][155].…”
Section: Transcriptional Control Of the Major Ie Genementioning
confidence: 99%
“…BMP, an important member of the transforming growth factor-β (TGF-β) family, represents a class of secreted glycoproteins that induce ectopic bone and cartilage formation, and it is involved in many important biological processes, such as embryonic development, cell differentiation, and organ formation[129]. BMP-7 has been shown to reduce macrophage infiltration and tissue damage in animal models of acute and chronic renal failure[130]. BMP-7 was originally approved in 2001 for the treatment of the nonunion of long bone fractures secondary to trauma, and it has also been studied in phase II/III trials for the treatment of periodontal disease.…”
Section: Csc Signaling Pathways and Inhibitorsmentioning
confidence: 99%
“…The PI3K/Akt signaling pathway is both a convergence and divergence point for many cell signals that regulate the phosphorylation of signaling molecules, and this pathway engages in crosstalk with the BMP/Smad and Wnt/β-catenin pathways, among others. Then, downstream signaling affects the expression of nuclear transcription factors, ultimately regulating cell proliferation, self-renewal, and multidirectional differentiation potential[130,131]. GDC-0084 (Figure 5), a small molecule inhibitor of the PI3K/AKT/mTOR pathway, is being studied in a phase II clinical trial for the treatment of glioblastoma multiforme (GBM).…”
Section: Csc Signaling Pathways and Inhibitorsmentioning
confidence: 99%
“…Moreover, BCAAs have been widely known to activate mammalian target of rapamycin (mTOR), which can modulate autophagy and inflammatory responses (Xu and Brink, 2016; Saxton and Sabatini, 2017; Sinclair et al, 2017). Reports have demonstrated that mTOR can facilitate PI3K/Akt-induced NF-κB activation (Peppenelli et al, 2018; Altman et al, 2019), an important step in all the three stages of HCMV infection (Li et al, 2015; Peppenelli et al, 2018; Altman et al, 2019) (). Consequently, targeting the PIK/Akt/mTOR cascade might be more efficient for treating HCMV-positive PSS.…”
Section: Discussionmentioning
confidence: 99%